2006
DOI: 10.1111/j.1525-1497.2006.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of handheld computers in medical education

Abstract: BACKGROUND: Over the past decade, handheld computers (or personal digital assistants [PDAs]) have become a popular tool among medical trainees and physicians. Few comprehensive reviews of PDA use in medicine have been published. OBJECTIVE: We systematically reviewed the literature to (1) describe medical trainees' use of PDAs for education or patient care, (2) catalog popular software applications, and (3) evaluate the impact of PDA use on patient care. DATA SOURCES: MEDLINE (1993 to 2004), medical educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
129
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 36 publications
6
129
2
4
Order By: Relevance
“…The survey form was based primarily on other surveys evaluating m-learning and the use of mobile devices in the medical fields. 5,6,[10][11][12]16,17 Students were asked to indicate the activities for which they used their devices, and the frequency of usage. The question asked was "Did you use your mobile device for any of the following during the year?"…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey form was based primarily on other surveys evaluating m-learning and the use of mobile devices in the medical fields. 5,6,[10][11][12]16,17 Students were asked to indicate the activities for which they used their devices, and the frequency of usage. The question asked was "Did you use your mobile device for any of the following during the year?"…”
Section: Methodsmentioning
confidence: 99%
“…Not entirely surprising, then, studies of clinical students' use of mobile devices have shown their increasing use and perception of value of the devices. 5,[12][13][14] For example, Strayer et al found as many as 59% of the medical students used their Personal Digital Assistants (PDAs) on a weekly basis, and 71% had loaded medical applications onto their PDAs, and accessed their web-based courses from their PDA significantly more than from other computing devices. 14 Crucial to the success of m-learning in the studies is the technical, financial and other support offered to the students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking specifically at medical students, Grasso et al (2005) surveyed preclinical and clinical medical students and found that the clinical students used drug references and medical calculators on their handheld device. Kho et al (2006) found that 60-70% of medical students and residents use PDAs for education or clinical care. At IUSM we were interested in how our third-year…”
Section: Introductionmentioning
confidence: 99%
“…In October 2010, another study showed that 85% of all American adults, 96% of those were aged 18-29 years, and 90% of those aged 30-49 years own a cell phone (Smith 2010a). Work has previously been done looking at the trends of handheld computing and mobile device use in graduate medical education (Barrett et al 2004;Sutton et al 2004;Mattana et al 2005;Khan et al 2007;Morris et al 2007), with undergraduate medical students (Grasso et al 2005;Kho et al 2006;Kennedy et al 2008;Norman et al 2008;Chatterley & Chojecki 2010;Ferenchick et al 2010;Lasserre et al 2010), and the health care setting (Garritty & El Emam 2006;Ranson et al 2007;Trelease 2008;Evans & Stacey 2009). Looking specifically at medical students, Grasso et al (2005) surveyed preclinical and clinical medical students and found that the clinical students used drug references and medical calculators on their handheld device.…”
Section: Introductionmentioning
confidence: 99%